Estudo do perfil dos pacientes com hipertensão arterial resistente atendidos no hospital universitário João de Barros Barreto - TAVARES, Dalila Pinheiro Diniz (2024)
Introduction: Hypertension (HTN) is a global public health concern, affecting approximately 1.28 billion adults worldwide. In addition to the serious complications of HTN, the challenge of Resistant Hypertension (RH) arises—a condition characterized by the inability to control blood pressure despite treatment with multiple medications. This study analyzed the profile of patients with RH at the João de Barros Barreto University Hospital (HUJBB), investigating comorbidities, treatment adherence, and intervention effectiveness. Objective: To analyze the profile of patients with RH at HUJBB, investigating their relationship with sex, age, most prescribed medications, treatment adherence, therapeutic efficacy, and comorbidities. Methodology: The study was cross-sectional, descriptive, and analytical, with the analysis of 238 medical records selected based on inclusion criteria, which included patients aged between 18 and 75 years, with RH, and treated between January 2020 and December 2021. Data on sex, age, treatment adherence, comorbidities, prescribed medications, and blood pressure levels before and after treatment were reviewed. The G-test and T-test of correlation were applied for statistical analysis. Results: The profile of analyzed patients with RH reveals a predominance of females, advanced age, the presence of dyslipidemia, and obesity. Treatment adherence had a significant impact on the classification of hypertension, with the majority of adherent patients now falling into less severe stages of the condition. The most common medication combinations included angiotensin receptor blockers, calcium channel blockers, and thiazide diuretics. Dyslipidemia and obesity were correlated with blood pressure levels before treatment, while diabetes and treatment adherence showed an association with blood pressure levels after treatment. Conclusion: The study unveiled a characteristic profile of patients with RH at HUJBB and emphasized the importance of treatment adherence and the appropriate choice of medications. These findings provide valuable insights for improving RH management and the development of effective prevention and treatment strategies.